2017
DOI: 10.1111/jne.12448
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Agonist Pasireotide Inhibits Exercise‐Stimulated Growth in the Male Siberian Hamster (Phodopus sungorus)

Abstract: 25The Siberian hamster (Phodopus sungorus) is a seasonal mammal, exhibiting a suite of 26 physiologically and behaviourally distinct traits dependent on the time of year and governed by 27 changes in perceived day length (photoperiod). These attributes include significant weight loss, 28 reduced food intake, gonadal atrophy, and pelage change with short day photoperiod as in winter. 29The central mechanisms driving seasonal phenotype change during winter are mediated by a 30 reduced availability of hypothalami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
(101 reference statements)
1
9
0
Order By: Relevance
“…This effective reversal of Dehnel's phenomenon has been observed in several seasonal rodent species, and upregulation of the growth axis was implicated in a series of experiments by Katarina Borer and colleagues in the Golden hamster in the 1970s 53 . In our experiments, we recently demonstrated that this exercise stimulated weight gain is associated with increased Ghrh , Npy and Pomc expression in the ARC in Siberian hamsters 50 . The ARC Ghrh expression was unaltered by somatostatin SSTR5 receptor antagonist pasireotide, indicating action downstream of this change in expression, perhaps unsurprising as it is not predicted to cross the blood–brain barrier.…”
Section: The Growth Axis and Exercisesupporting
confidence: 70%
See 4 more Smart Citations
“…This effective reversal of Dehnel's phenomenon has been observed in several seasonal rodent species, and upregulation of the growth axis was implicated in a series of experiments by Katarina Borer and colleagues in the Golden hamster in the 1970s 53 . In our experiments, we recently demonstrated that this exercise stimulated weight gain is associated with increased Ghrh , Npy and Pomc expression in the ARC in Siberian hamsters 50 . The ARC Ghrh expression was unaltered by somatostatin SSTR5 receptor antagonist pasireotide, indicating action downstream of this change in expression, perhaps unsurprising as it is not predicted to cross the blood–brain barrier.…”
Section: The Growth Axis and Exercisesupporting
confidence: 70%
“…When given access to a running wheel, the Siberian hamster will spontaneously run for long periods of time during their normally active phase (night), and for hamsters housed in long or short photoperiod they will equally run for 10–15 km per day 50 . Interestingly, this is accompanied with weight gain in short day (or winter) acclimated hamsters, 42,51 probably through increased food intake.…”
Section: The Growth Axis and Exercisementioning
confidence: 99%
See 3 more Smart Citations